2022
DOI: 10.3390/pharmaceutics14102193
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Biorelevant Hydrodynamic Conditions on Drug Dissolution from Extended-Release Tablets in the Dynamic Colon Model

Abstract: The in vitro release of theophylline from an extended-release dosage form was studied under different hydrodynamic conditions in a United States Pharmacopoeial (USP) dissolution system II and a bespoke in vitro tubular model of the human colon, the Dynamic Colon Model (DCM). Five biorelevant motility patterns extracted from in vivo data were applied to the DCM, mimicking the human proximal colon under baseline conditions and following stimulation using polyethylene glycol or maltose; these represent the lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Figure 3 shows the predictions of theophylline Cp–time profiles after administration of the Uniphyllin Continus ® 200 mg tablet bis in die (b.i.d) for 5 days, with a single dose on day 6 [ 41 ] using the USP II and DCM dissolution profiles as published by O’Farrell et al [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Figure 3 shows the predictions of theophylline Cp–time profiles after administration of the Uniphyllin Continus ® 200 mg tablet bis in die (b.i.d) for 5 days, with a single dose on day 6 [ 41 ] using the USP II and DCM dissolution profiles as published by O’Farrell et al [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The simulations also showed that three different motility patterns (baseline, antegrade and retrograde) could explain the level of exposure of theophylline after oral administration of the Uniphyllin Continus ® tablet. However, O’Farrell et al [ 36 ] showed differences in the distribution of theophylline throughout the DCM after applying different motility patterns. The average dissolution profiles resulting from the baseline, antegrade and retrograde waves were similar.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations